World Religions the Spirit Searching - Ondich, Jody (Open textbook library., 2021)
Humans across the globe and throughout millennia have searched for answers to questions like, "why are we here?" or "what am I supposed to do with my life?" And the answers people have found, or created, or chosen, have varied as widely as the cultures and people themselves. Some people focus on rules. Some focus on afterlives. Some look to become whole. Some seek adventure and learning. So this text, while full of various ways that people have searched and discovered and created, is only touching a few of the bigger traditions in our world. Hopefully each chapter will introduce the reader to some ideas from that specific tradition that enlighten them as to how a specific group of people think, believe, and live. This text is set up to be an ebook. The various videos, links and resources will only really work if the user keeps to the digital format. Read this book on a device--it will be a much more rewarding experience!